Engineered Water Highways in Fuel Cells: Radiation Grafting of Gas Diffusion Layers. (23rd September 2015) - Forner‐Cuenca, Antoni; Biesdorf, Johannes; Gubler, Lorenz; Kristiansen, Per Magnus; Schmidt, Thomas Justus; Boillat, Pierre
Abstract : A novel method to produce gas diffusion layers with patterned wettability for fuel cells is presented. The local irradiation and subsequent grafting permits full design flexibility and wettability tuning, while modifying throughout the whole material thickness. These water highways have improved operando performance due to an optimized water management inside the cells.